SPS-Bansho untuk Meningkatkan Aktivitas Belajar Matematika Peserta Didik SMPN 18 Tangerang - Dyah Sinto Rini (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
This article is a best practice implemented by applying the learning model of SPS-Bansho (Structured Problem Solving using Bansho) at SMPN 18 Tangerang. This best practice has succeeded in increasing students’ mathematics learning activities during the learning process. The observation sheet was used to observe the students’ mathematics learning activities. All indicators of students’ mathematics learning activities were observed during the learning process. Students were challenged more to ask questions during a group or class discussions. They were able to respond to their friends' opinions well, participate in groups, and help friends in completing assignments. Students presented their work in front of the class, and they could summarize the material they have learned.